FAKTOR BERALIHNYA TENAGA KERJA ANAK PETANI KE SEKTOR NON-PERTANIAN DI DESA TREMAN KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - Aprilia Deasi Wehantouw; Elsje Pauline Manginsela; Vicky R. B. Moniaga (Sam Ratulangi University, 2018)
This study aims to increase the knowledge regarding determinant factors causes the shift of youth labor as farmersâ€™ children to non-agricultural sector. The location of the research was conducted in Treman Village,Â Kauditan District, North Minahasa Regency. The study was conducted from January to June 2018. The data used were primary and secondary data. Number of child farmers as the selected respondents are 18 people representing XVIII Jaga by using purposive sampling method. Data analysis used descriptive qualitative analysis in the form of tables and simple quantitative calculations. The results showed that there are two groups of factors causing the shift of child labor of farmers to non-agricultural sector. The first group is the push factor which consists of (1) the conversion of agricultural land to non-agriculture such as the displacement of agricultural land for the construction of buildings and roads which result in the narrowing of the availability of working and working fields, (2) lack of understanding and willingness to work in the agricultural sector. While the second group is the pull factor, consisting of (1) the wage/salary rate in the agricultural sector is lower than wages in the non-agricultural sector. (2) Peasant children's views on employment in non-agricultural and agricultural sectors. There are four views expressed by the child farmers are: a. work in accordance with the field of science related to non-agriculture because according to the last education that has been taken, b. working in the non-agricultural sector is more appreciated and raises social status, c. want to improve working experience in non-agricultural sector, d. better working conditions in non-agriculture than the conditions of employment in agriculture. (3) the more open the opportunities for business and work and the more choices of types of business and work available in the non-agriculture sector than in the agricultural sector.*eprm*.